2006
DOI: 10.3200/jach.55.2.83-90
|View full text |Cite
|
Sign up to set email alerts
|

International Study of Heavy Drinking: Attitudes and Sociodemographic Factors in University Students

Abstract: The authors studied the prevalence of heavy drinking among students in 21 developed and developing countries using an anonymous survey of 7,846 male and 9,892 female students aged 17 to 30 years. There were wide variations in the prevalence of drinking among countries, and the highest rates of heavy drinking (defined as 5 or more drinks for men and 4 or more drinks for women on at least 1 occasion over the past 2 weeks) were reported in Belgium, Colombia, Ireland, and Poland (men), and Ireland and England (wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
96
4
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 27 publications
11
96
4
6
Order By: Relevance
“…In this study, however, this background was not, among the men, associated with engaging in monthly HED, as has been the case in studies from high-income settings (Dantzer et al, 2006;Humensky, 2010). Among the women, the results partially agree with the findings from affluent societies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, however, this background was not, among the men, associated with engaging in monthly HED, as has been the case in studies from high-income settings (Dantzer et al, 2006;Humensky, 2010). Among the women, the results partially agree with the findings from affluent societies.…”
Section: Discussionsupporting
confidence: 80%
“…Our analyses showed that students from a more affluent and less traditional background-that is, those who were brought up in a relatively secular environment by well-educated parents-were more likely to use alcohol, which matches findings from higher-income settings (Dantzer et al, 2006;Silva, Malbergier, Stempliuk, & de Andrade, 2006). In this study, however, this background was not, among the men, associated with engaging in monthly HED, as has been the case in studies from high-income settings (Dantzer et al, 2006;Humensky, 2010).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The percentage of students (40 %) in the present study was also higher than the percentage of students in the HET (10 %). Alcohol habits among students have been studied earlier [28][29][30][31]. Dantzer et al…”
Section: Discussionmentioning
confidence: 99%
“…For example, the perception that limiting alcohol consumption benefits health, correlates negatively with alcohol intake among university students [10]. Among adolescents in the Netherlands perceptions on the risk to become nicotine addicted predicted abstinence of cigarette smoking [11].…”
Section: Introductionmentioning
confidence: 99%